Revitalisasi Maqasid Al-Shari’ah: Pembacaan Ulang Konsep Kewarisan Beda Agama - Baihaqi, Wahid Ahtar (IAIN Ponorogo, 2017)
Abstract: Embryo of maqasid shari’ah as a value has emerged since the 3rd islamic century and recently transformed into an approach in the hands of al-Shatibi. Al-Shatibi’s brilliant idea was more comprehensively developed so that becomes an approach to formulating Islamic law by contemporary Maqasidiyyun schoolars who one of them is Yusuf Qardawi. In the case of inheritance of different religions, al-Qardawi opinionated that a Moslem can inherit treasure to non-Moslems, because of there is greater benefit in that maslahah dimension. In operations, al-Qardawi do takwil the hadith used by the majority of fuqaha (Islamic jurists), as the reason for the prohibition of inherit treasure due to different religions. The efforts of al-Qaradawi are classified in tarjih bi al-maqasid al-shari’ah, which emphasizes maslahah as the last consideration in the establishment of Islamic law. It means that, if the Islamic law can not realize maslahah as the final purpose, then it should switch to the other options which can bring on maslahah. Abstrak: Embrio maqa>>sid shari>’ah sebagai sebuah nilai telah muncul sejak abad 3 H dan baru bertransformasi menjadi sebuah pendekatan di tangan al-Sha>tibi>. Ide brilian al-Sha>tibi> itu kemudian dikembangkan lebih komprehensif sehingga menjadi sebuah pendekatan dalam merumuskan hukum Islam oleh ulama Maqa>>sidiyyu>n kontemporer, salah satunya pakar hukum Islam adalah Yu>suf al-Qarda>wi>. Dalam permasalahan kewarisan beda agama, al-Qarda>wi> berpendapat bahwa seorang muslim dapat mewarisi harta non muslim, dengan alasan dimensi kemaslahatan di dalamnya lebih besar. Karena mengambil harta tersebut lebih baik daripada membiarkan berada di tangan non muslim yang bisa digunakan dalam hal kemaksiatan atau membahayakan orang Islam. Dalam operasionalnya, al-Qarda>wi> melakukan takwi>l terhadap hadi>th yang digunakan oleh mayoritas fuqaha sebagai alasan larangan mewarisi disebabkan perbedaan agama. Upaya al-Qarda>wi> tersebut tergolong dalam tarji>h bi al-Maqa>>sid al-Shari>’ah, yang menekankan kemaslahatan sebagai konsiderasi terakhir dalam penentuan hukum. Artinya, apabila suatu hukum tidak dapat merealisasikan kemaslahatan sebagai tujuan akhir, maka harus beralih pada opsi yang dapat berdampak pada kemaslahatan.